The Influence of Service Marketing Mix on The Decision of Patients to Choose Any Types of Service at SMEC Medan Hospital, in 2018 - Ciatawi, Thamrin (Sari Mutiara Indonesia University Press, 2018)
Market for health care is centered in consumers, and it is expected to have the best service quality with the cost as minimal as possible. Hospital management should know marketing factors which will influence patients and services in choosing hospital types of service. Marketing mix strategy is focused on basic practice which should be done by every company by identifying consumers, finding out consumers’ needs and preferences, analyzing some factors which influence consumers’ decision, and persuading consumers to buy its products and services. The objective of the research was to find out the influence of service marketing mix on patients’ decision to choose any types of service at SMEC Hospital, in 2018. The research used analytic study method with case-control design. The samples were taken by using consecutive sampling technique with respondents who met inclusion and exclusion criteria. The respondents were 45 SMEC BPJS patients and 45 SMEC Executive patients. The result of bivariate analysis showed that there was significant relationship of product, people, process, and physical evidence with respondents’ decision to choose the SMEC Executive types of service. The result of multivariate analysis showed that there was significant relationship of people and process with respondents’ decision to choose the SMEC Executive types of service, and the variable of people were the most dominant factor. The research concluded that product, people, process, and physical evidence had influence on the decision to choose the types of service in the hospital, and while people were the most influential factor. Researcher suggested that hospitals could maintain and improve the factor of people’s quality because people were the most dominant factor, and along by increasing the other factors in order to help achieving hospital’s goals. Besides that, other researchers can observe the variables with different settings of locations, so it won’t cause bias of data, multi-centered, and with a larger number of samples.